2020
DOI: 10.20944/preprints202002.0338.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantum Cognitive Triad: Semantic Geometry of Context Representation

Abstract: The paper describes an algorithm for semantic representation of behavioral contexts relative to a dichotomic decision alternative. The contexts are represented as quantum qubit states in two-dimensional Hilbert space visualized as points on the Bloch sphere. The azimuthal coordinate of this sphere functions as a one-dimensional semantic space in which the contexts are accommodated according to their subjective relevance to the considered uncertainty. The contexts are processed in triples defined by knowledge o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(23 citation statements)
references
References 101 publications
(151 reference statements)
0
23
0
Order By: Relevance
“…Unlike standard Euclidean geometry, orthogonality of the qubit states corresponds to the opposite orientation, as seen for basis vectors 0|1 = 0, pointing to the poles of the sphere. By representing context in relation to the basis decision to be made, the qubit state (Equation 1) encodes its meaning in subjective experience of the considered person (Surov, 2022).…”
Section: Representation Of Contexts By Qubit Statesmentioning
confidence: 99%
See 3 more Smart Citations
“…Unlike standard Euclidean geometry, orthogonality of the qubit states corresponds to the opposite orientation, as seen for basis vectors 0|1 = 0, pointing to the poles of the sphere. By representing context in relation to the basis decision to be made, the qubit state (Equation 1) encodes its meaning in subjective experience of the considered person (Surov, 2022).…”
Section: Representation Of Contexts By Qubit Statesmentioning
confidence: 99%
“…2). While maintaining key features of the quantum approach such as contextuality, superposition, and entanglement, it is unique in allowing simple geometrical representation, recently interpreted as an individual semantic space (Surov, 2021). Furthermore, the qubit structure is shown to encode elementary states of emotional experience (Surov, 2022).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The identification of the presence of quantum structures in human cognition, and its importance for the development of performant quantum structure-based models for bounded rationality situations and human decisions, led to a field of research now called 'quantum cognition' (Aerts & Aerts, 1995;Gabora & Aerts, 2002;Bruza & Cole, 2005;Aerts & Gabora, 2005a,b;Busemeyer et al, 2006;Bruza & Gabora, 2009;Aerts, 2009a,b;Aerts & Sozzo, 2011;Aerts et al, 2012;Busemeyer & Bruza, 2012;Haven & Khrennikov, 2013;Dalla Chiara et al, 2015;Pothos et al, 2015;Blutner & beim Graben, 2016;Moreira & Wichert, 2016;Gabora & Kitto, 2017;Surov, 2021;Pothos & Busemeyer, 2022). Parallel to the emergence of the research field of quantum cognition, quantum structures were identified in computer science, their use especially in information retrieval and natural language processing leading to important results, and also bringing a new research domain to life called 'quantum information science' (Aerts & Czachor, 2004;Van Rijsbergen, 2004;Widdows, 2004;Song et al, 2010;Melucci, 2015;Aerts et al, 2019).…”
Section: Introductionmentioning
confidence: 99%